BBT405 – Plant Tissue Culture (Tisu Kultur Tumbuhan) July/August 2023 - Pusat Pengajian Sains Kajihayat, PPSK (Universiti Sains Malaysia, 2023)
Second Semester Examination 2023/2023 Academic Session July/August 2023 BBT405 – Plant Tissue Culture (Tisu Kultur Tumbuhan) Duration: 2 hours (Masa: 2 jam)